Predictive and prognostic impact of primary tumor‐bearing lobe in nonsmall cell lung cancer patients treated with anti‐PD‐1 therapy. Issue 8 (18th May 2020) - Takamori, Shinkichi; Takada, Kazuki; Shimokawa, Mototsugu; Matsubara, Taichi; Haratake, Naoki; Miura, Naoko; Toyozawa, Ryo; Yamaguchi, Masafumi; Takenoyama, Mitsuhiro; Yoneshima, Yasuto; Tanaka, Kentaro; Okamoto, Isamu; et al.
Abstract: Immunotherapy targeting programmed cell death‐1 (PD‐1) has become a standard pharmacological therapy. Although tumor mutation burden level was reported to depend on the tumor location in nonsmall cell lung cancer (NSCLC), predictive impact of the tumor location on the response to anti‐PD‐1 therapy is unknown. Two hundred and seventeen advanced or recurrent NSCLC patients treated with anti‐PD‐1 therapy at Kyushu University Hospital and National Hospital Organization Kyushu Cancer Center were analyzed. To minimize the bias arising from the patients' background, adjusted Kaplan‐Meier survival curves and Cox proportional hazards regression analyses using inverse probability of treatment weights (IPTW) were performed. Of the 217 patients, 132, 27, and 58 had primary NSCLC in upper, middle, and lower lobes, respectively. Patients with NSCLC in upper lobe were significantly associated with younger age ( P = .0070) and smoker ( P = .0003). The epidermal growth factor receptor ‐wild type and tumor location in upper lobe were independent predictors of disease control ( P = .0175 and P = .0425, respectively). The IPTW‐adjusted Kaplan‐Meier curves showed that patients with NSCLC in the upper lobes had significantly longer progression‐free survival (PFS) and overall survival (OS) than those in middle/lower lobes ( P = .0026 and P = .0015, respectively). On IPTW adjusted Cox analysis, NSCLC in the upper lobe was an independent predictor of PFS and OS ( P = .0078 and P = .0034, respectively). Patients with primary NSCLC in the upper lobes may be good candidates for anti‐PD‐1 therapy. These findings should be validated prospectively. Abstract : What's new? Tumor mutation burden (TMB) can predict clinical benefit of anti‐programmed death‐1 (anti‐PD‐1) immunotherapy in non‐small cell lung cancer (NSCLC) patients. Evidence suggests that TMB depends on tumor location, though whether tumor location influences anti‐PD‐1 drug efficacy is unclear. This study shows that tumor location in the upper lobe of the lung independently predicts disease control by anti‐PD‐1 therapy in NCSLC patients. Patients with tumors in the upper lobes exhibited improved progression‐free and overall survival compared to patients with tumors in the middle or lower lobes. The findings identify potential benefits of anti‐PD‐1 therapy based specifically on NSCLC location.